Ability to generalize in foreign language of the first years students in the higher educational institutions - Mylnikova, Nataliia (Social Welfare: Interdisciplinary Approach, 2013)
The article presents an overview of works of the foreign and national psychologists that carry out search of opportunities to optimize the system of specialists training in foreign language, clarify specifc character of generalization processes infuence within learning of a foreign language in traditional and modern psychological science, provide empirical studies of qualitative indicators of this phenomenon.
Keywords: ability to generalize; empirical thinking; classifcation; image; practical thinking; theoretical thinking